Analisis Kompetensi Digital Akuntan Muda dalam Menghadapi Perkembangan Teknologi - Tommy Ferdian; Ronald N Girsang; Gita Suliska (Universitas Tridinanti, 2026)
The development of digital technology has transformed accounting, taxation, and auditing practices through the use of applications, cloud systems, and system automation. This study aims to analyze the digital competence of young accountants in facing technological development, particularly in the use of Accurate, Accurate Online, Coretax, Excel, and technology-based audit applications. This research uses a qualitative approach with a case study method through literature review, students’ internship experiences, and interviews with accounting alumni and students. The results show that digital applications have supported transaction input, data processing, tax reporting, cost monitoring, and financial report preparation. However, the digital competence of young accountants remains suboptimal because application mastery is mostly obtained through work practice, internships, self-learning, tutorials, and guidance from colleagues. The use of technology-based audit applications is also still limited. The implication of this study indicates the need to strengthen curricula, training, certification, and technology-based internship collaboration so that young accountants are better prepared to face digital transformation. Abstrak Perkembangan teknologi digital telah mengubah praktik akuntansi, perpajakan, dan audit melalui penggunaan aplikasi, cloud, serta otomatisasi sistem. Penelitian ini bertujuan menganalisis kompetensi digital akuntan muda dalam menghadapi perkembangan teknologi, khususnya pada penggunaan Accurate, Accurate Online, Coretax, Excel, dan aplikasi audit berbasis teknologi. Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus melalui studi literatur, pengalaman magang mahasiswa, dan wawancara dengan alumni serta mahasiswa akuntansi. Hasil penelitian menunjukkan bahwa aplikasi digital telah membantu penginputan transaksi, pengolahan data, pelaporan pajak, monitoring biaya, dan penyusunan laporan. Namun, kompetensi digital akuntan muda masih belum optimal karena penguasaan aplikasi lebih banyak diperoleh melalui praktik kerja, magang, belajar mandiri, tutorial, dan bimbingan rekan kerja. Penggunaan aplikasi audit berbasis teknologi juga masih terbatas. Implikasi penelitian ini menunjukkan perlunya penguatan kurikulum, pelatihan, sertifikasi, dan kerja sama magang berbasis teknologi agar akuntan muda lebih siap menghadapi transformasi digital.